2002
DOI: 10.1149/1.1507593
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Method to Estimate Ion Size for Electrolyte Materials Design

Abstract: Ion size is an important parameter in interpreting the electrochemical properties of the electrolyte materials. There is difficulty in selecting a representative value for ionic radius when the ion has a shape far from spherical. Since the van der Waals volume becomes a good parameter for ion size, it was calculated by numerical integral based on a simple overlapped spherical model using the optimized structures by ab initio molecular orbital calculation. We have examined the extent of errors affected by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
172
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 206 publications
(186 citation statements)
references
References 22 publications
13
172
1
Order By: Relevance
“…According to ab initio molecular orbital calculation by Ue et al [16], the cation (Et 4 N + ) and the anion (BF 4 − ) of the electrolyte in the present study have respective solvated sizes of 0.68 and 0.44 nm in propylene carbonate. The simple sum of both ions corresponding to the size of their ion pair is estimated to be 1.12 nm, which is certainly larger than the average pore diameter of M500.…”
Section: The Penetration Of the Electrolyte Into The Poresmentioning
confidence: 60%
“…According to ab initio molecular orbital calculation by Ue et al [16], the cation (Et 4 N + ) and the anion (BF 4 − ) of the electrolyte in the present study have respective solvated sizes of 0.68 and 0.44 nm in propylene carbonate. The simple sum of both ions corresponding to the size of their ion pair is estimated to be 1.12 nm, which is certainly larger than the average pore diameter of M500.…”
Section: The Penetration Of the Electrolyte Into The Poresmentioning
confidence: 60%
“…Figure 2c and d shows that torsional actuation and yarn tensile actuation are correlated and both depend on the size of the electrolyte ion used to compensate electronic charge. When a 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl) imide (BMP.TFSI) electrolyte was used (Figure 2c), which has similar van der Waals volumes [18] of the anion (147 Å 3 ) and cation (167 Å 3 ), similar torsional and tensile actuation was shown at both positive and negative potentials. Likewise, the much large actuation during reduction than for oxidation in Figure 2d for the TBA.PF 6 electrolyte reflects the larger unsolvated van der Waals volume [18] for the TBA cation (293 Å 3 ) than for the PF 6 anion (69 Å 3 ).…”
Section: Reviewmentioning
confidence: 99%
“…When a 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl) imide (BMP.TFSI) electrolyte was used (Figure 2c), which has similar van der Waals volumes [18] of the anion (147 Å 3 ) and cation (167 Å 3 ), similar torsional and tensile actuation was shown at both positive and negative potentials. Likewise, the much large actuation during reduction than for oxidation in Figure 2d for the TBA.PF 6 electrolyte reflects the larger unsolvated van der Waals volume [18] for the TBA cation (293 Å 3 ) than for the PF 6 anion (69 Å 3 ). While these advances using liquid electrolytes are fundamentally important (and use of the torsional muscles in a microfluidic circuit was demonstrated) [1], more general practical utilization is restricted by the use of a liquid electrolyte bath and the associated need for a containment system, which dramatically degrades the gravimetric and volumetric performance of the overall actuator device.…”
Section: Reviewmentioning
confidence: 99%
“…This behavior can be explained by the thinner double-layer being due to the higher ionic concentration than that of nonaqueous solutions. However, the correlation between the doublelayer capacitance and anion size [41] observed in PC solutions [8] is not clear. It was further shown that the double-layer capacitance of the ionic liquid was not dependent on the choice of electrode from among DME, GC, and activated carbon fiber [31].…”
Section: Double-layer Capacitancementioning
confidence: 99%
“…This observation is attributed to the ''ionsieving effect'' of the activated carbons because EMI þ (V c ¼ 116 Å 3 ) is smaller than Et 4 N þ (159) [41]. The smaller anion also affords higher capacitance in the following order [51]: EMIBF Figure 17.7 shows the change of the capacitances of the double-layer capacitors using various electrolytes, when operating temperature was varied from 25 to À25 C. The capacitance of all ionic liquids decreased rapidly compared with the 1 M Et 3 MeNBF 4 /PC due to the increase of internal resistance reflecting the temperature dependence of electrolytic conductivity in Figure 17.4.…”
Section: Initial Characteristicsmentioning
confidence: 99%